Application of Information Technology in Administrative Services at the Population and Civil Registration Office of Badung Regency - Pramesti, Ni Putu Dinda Puspa; Wirantari, I Dewa Ayu Putri (Westscience Press, 2025)
The application of information technology in population administration services is one of the strategic efforts to improve the quality, efficiency, and effectiveness of public services. This study aims to examine the implementation of information technology at the Population and Civil Registration Office of Badung Regency, especially in the use of the online application